Hard-template synthesis of three-dimensional mesoporous Cu–Ce based catalysts with tunable architectures and their application in the CO catalytic oxidation. Issue 69 (6th July 2016) - Li, Liyan; Han, Weiliang; Tang, Zhicheng; Zhang, Jiyi; Lu, Gongxuan
Abstract : In this paper, 3D Cu–Ce-Ox catalysts with different pores were synthesized by controlling the calcination temperaturre. The CeCu20-600 showed the highest catalytic activity, where CO can be fully oxidized at 55 °C and expressed good stability. Abstract : In this paper, three-dimensional (3D) Cu–Ce-Ox catalysts with controllable pore diameters were rationally designed and synthesized by a facile hard-template method. By controlling the calcination temperature, the 3D Cu–Ce-Ox catalysts with different pores were synthesized by nano-replication technology with KIT-6 as hard template. These catalysts expressed 3D pore structure, possessed higher pore volume and large pores, and owned more surface active sites, which were helpful for CO oxidation. When the calcination temperature of Cu–Ce-Ox was 600 °C, this catalyst showed the highest catalytic activity. The reason was due to its relatively stronger redox ability and surface activity species. More Ce 3+, Cu + and chemisorbed oxygen concentration was very useful in achieving the highest catalytic performance.